Iqlim o'zgarishi natijasida xavfli gidrometeorologik hodisalarning o'zgarishini baholash (Qoraqalpog'iston Respublikasi) misolida - Omonboyev Sh.D (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article is about climate change in the world, the causes of changes in meteorological phenomena, and the increasing danger of meteorological phenomena, the opinions and reflections of scientists of our country on the causes of climate change, samples of scientific research, and hydrometeorological statistical data. Moreover, we will find answers to questions about how solutions to climate change problems are being implemented in the Republic of Karakalpakstan.